Desenvolvimento de uma tecnologia para sistematização da assistência de enfermagem à mulher no trabalho de parto de parto e parto - Shinkai, Michelle Prudencio (2024)
The objective of this study was to develop a Technology aimed at the Systematization of Nursing Care for women in labor and delivery, based on the Theory of Basic Human Needs (NHB). This is a methodological study, with a quantitative approach, developed in three stages, namely: integrative literature review, content evaluation and instrument development. For the methodological path, the theoretical framework of Echer, Oliveira and Lucena (2014) and Silva et al (2020) was used to develop the technology and the Delphi On line Technique to evaluate the content. In the first stage, an integrative review was carried out in search of the main nursing diagnoses aimed at women in labor and delivery through the CAPES portal, CAFe access, to the following databases: Scielo (Scientific Electronic Library Online); Lilacs (Latin American and Caribbean Literature in Health Sciences); Medline (Medical Literature Analysis and Retrievel System Online), BDENF (Nursing Database), Web of Science, CINAHL (Cumulative Index to Nursing and Allied Health Literature), SCOPUS (Scopus Info Site), BDTD (Brazilian Digital Library of Theses and Dissertations and OATD (Open Access Theses and Dissertations), with the analysis of scientific production developed with the support of the RAYYAN software. The search was carried out with the following descriptors: Nursing Diagnosis, Nursing Process, Nursing Care, Pregnant Women, Pregnancy , Women, Maternal Health, Labor, Childbirth, Normal Birth, Obstetrics, Nursing, Obstetric Nursing. As a result of this stage, 16 publications were included, resulting in the occurrence of 48 nursing diagnoses related to assistance to women during childbirth, using the cross-mapping technique between the diagnoses (NANDA and CIPE®) was used through the focus axis. In the second stage, the evaluation of these diagnoses was carried out with 53 judges, carefully selected from the database of the National Council for Scientific and Technological Development (CNPq), by filling out an online form on Google Forms where, using a Likert scale and an open question for suggestions, nursing diagnoses were evaluated and modifications were suggested. The analysis of consensus and dissent occurred by calculating the Agreement Index >90%. In the third stage, the instrument was developed according to the stages of the Nursing Process (NP), based on: publications on the topic; in the NANDA nursing diagnoses (2021-2023) validated in the previous stage; interventions selected from the Nursing Intervention Classification (NIC, 2020) and; results from the Nursing Outcome Classification (NOC, 2020), in addition to the researcher's clinical experience and relevant literature. The domains of the instrument, for the first stage of the nursing process, were categorized by Wanda de Aguiar Horta's NHB Theory. It is expected that the technology will be used by nurses, supporting childbirth care and contributing to future research.